Interactive platforms and knowledge management strategies during Covid-19 - González-Díaz, Romel Ramón; Vásquez Llamo, Carlos Enrique; Hurtado Tiza, David Raúl; Menacho Rivera, Alejandro Sabino (Revista Venezolana de Gerencia, 2020)
<span style="color: #222222; font-family: Arial, sans-serif; font-size: 9px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: 10.8px; orphans: 2; text-align: justify; text-indent: 14px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; display: inline !important; float: none;">This research aimed to analyze the relationship between the use of educational platforms y knowledge management strategies during periods of social confinement. A survey composed of 26 items with a Likert scale was applied, validated in the opinion of 3 experts with a Cronbach’s Alpha coefficient of 0.906 (Excellent). A random sample was estimated with a margin of error of 10% y a confidence level of 90%, applying a total of 132 surveys to teachers in the period from 04/01/2020 to 05/15/2020. The data were analyzed by means of descriptive statistics to know the behavior of the variables under study, then the chi-square statistic was applied) in order to test the hypotheses by means of chi-square. It is concluded that the official educational institutions studied through the teaching staff and students do not use interactive platforms, alleging resistance to said change and revealing a challenge for school entities. The institutions studied should be able to reconcile rigid positions and accept new forms of learning experiences, revealing the imminent need for the educational crisis caused by Covid-19.